Data for the scientific article "Evaluating created wetlands for bird diversity and reproductive success" - Kačergytė, Ineta (Swedish University of Agricultural Sciences, 2021)
The conducted study was done in order to investigate what habitat characteristics could explain breeding wetland bird diversity and reproductive success in created wetlands in Uppland, Sweden. The geographical study units were individual wetlands. For each wetland, the data contains all environmental variables considered and estimated within the study (Landscape forest within 1 km buffer, Urban area within 1km buffer, Neighbouring wetlands within 3 km buffer, Size, area of open islands, area of wooded islands, Water vegetation, Local forest (50 m around shoreline), Flooded area, Year of creation, Inflow of water from other sources, Number of ponds within the wetlands, and whether the wetland is managed), as well as species richness, pair abundance, chick abundance and information on whether species succeeded to reproduce.

Data: data contains bird inventories in created wetlands in Uppland, Sweden.

Data collection description:
Four standardised wetland bird inventories of the 89 created biodiversity wetlands in Sweden took place during the breeding season in 2018: twice during the period when birds were settling or started breeding (14-29 May, "settlement stage"), and twice during the chick-rearing period (18 June - 3 July, "reproductive stage"). The data includes all wetland species except for passerines, and was counting pairs and chicks.

The variables are described in detail in the documentation file.

A file with geographical coordinates for the wetlands, bird_diversity_created_wetlands_coordinates.csv, is included.

A raw data file including migratory species and species information for each visit is available upon request.

Syftet med den genomförda studien var att undersöka vilka habitat- eller landskapsvariabler som kan förklara mångfalden av våtmarksfåglar och deras häckningsframgång i anlagda våtmarker i Uppland, Sverige. Den geografiska undersökningsenheten är de enskilda våtmarkerna. Uppgifterna för varje våtmark innehåller alla miljövariabler som tagits fram och undersökts i studien (andel skog inom 1 km från våtmarken, andel urban miljö inom 1 km, antal våtmarker inom 3 km, våtmarkens storlek, område öar utan busk- eller trädvegetation, område öar med busk- eller trädskikt, vattenvegetation, andel skog inom 50 m, översvämmad areal, år när våtmarken anlades, om det fanns tillflöde till våtmarken, antal dammar som våtmarken består av, om det utfördes habitatåtgärder), antal arter, antal par, antal ungar, samt information om huruvida arter lyckades producera ungar.

Data: data består av observationer från inventeringar av fåglar i anlagda våtmarker i Uppland, Sverige
Datainsamling:
För inventeringarna valdes 89 våtmarker som anlagts i naturvårdssyfte med målet att öka den biologiska mångfalden. I dessa 89 våtmarker inventerades våtmarksfåglar under fyra standardiserade inventeringstillfällen under fåglarnas häckningssäsong år 2018: två gånger under perioden när fåglarna etablerade revir på våren eller påbörjade häckningen (14-29 maj, "etableringsfas") och två gånger under perioden när ungar matas och fram till de blir flygga (18 juni - 3 juli, "reproduktiv fas”). Uppgifterna inkluderar alla arter av våtmarksfåglar förutom tättingar, och avser antal par och antal ungar per art.

Variablerna beskrivs detaljerat i dokumentationsfilen.

Fil med geografiska koordinater för de studerade områdena, bird_diversity_created_wetlands_coordinates.csv, ingår.

Rådatafil med artinformation kan tillhandahållas på begäran.
Data till den vetenskapliga artikeln "Evaluating created wetlands for bird diversity and reproductive success"
Keywords: wetland; våtmarker; habitat landscape metrics; birds presence; wetland ecology; birds abundance; Natural Sciences; Naturvetenskap; Environmental Sciences; Miljövetenskap; Ecology; Ekologi